Cinderella - Amery, Heather; Cartwright, Stephen, 1947- (Tulsa, Okla. : EDC, 2003)
A young girl who is forced to work while her ugly stepsisters play gets a chance to go to the ball with the help of her fairy godmother.
2.2
K-3
Keywords: Fairy tales; Folklore -- France; Fairy tales; Folklore -- France; Fairy tales; Folklore -- France; Fairy tales